Wraparound Chimeric Radial Collateral Artery Perforator Flap for Reconstruction of Thumb Loss - Song, Dajiang; Xu, Jian; Lv, Hongbin; Liu, Jun; Li, Jinsong (Journal of Reconstructive Microsurgery, 2015)
Objective We present our clinical experience and demonstrate surgical methods to reconstruct the thumb by using a wraparound chimeric radial collateral artery perforator flap.Methods Surgical procedures were performed in 12 patients. Flaps with a skin paddle and humeral bone segment were created on the basis of independent perforators. The sizes of the flaps and humeral fragments ranged from 5.5 cm × 2.0 cm to 7.5 cm × 4.5 cm and from 1.5 cm × 0.5 cm to 4.5 cm × 1.5 cm, respectively. The flap pedicle was divided and ligated above the level at which the radial collateral artery was divided into anterior and posterior branches. The following recipient vessels were used: (1) the proper radial digital artery of the thumb and the palmar subcutaneous vein (n = 8) and (2) the radial artery (n = 4) and the venae comitantes. Nerve suture was conducted between the posterior cutaneous nerve of the arm and the proper ulnar digital nerve of the thumb. The cosmetic appearance of the donor and recipient sites and the static two-point discrimination of the operated finger were evaluated in a follow-up visit.Results Postoperative venous congestion occurred in one case, but this complication was successfully treated after surgery. All of the flaps survived and all of the donor sites were closed directly, leaving a linear scar. Follow-up time ranged from 12 to 28 months. The union of bone components was observed in all of the cases at an average period of 4.5 months (range 3–6 months). Flap defatting was performed in two cases during the late postoperative period. Cosmetically acceptable results were achieved for the rest of the patients. The average of the static two-point discrimination scores was 9 mm (range 7–10 mm).Conclusions The wraparound chimeric radial collateral artery perforator flap could be an effective option for thumb reconstruction because no major donor-site complications were found.
Keywords: radial collateral artery; chimeric flap; thumb loss; wraparound flap